The Sustainable Tourism Potential Of The “1000 STEPS” In Sitio Natipunan, Ifugao: An ASEAN Standard Community-Based Tourism Assessment - Piyaje W. Mahingyan; Angelika B. Valiente; Raiza G. Paransac; Apple B. Bucad; Rhoann P. Santos; Emanuel A. Gamiao; Client William M. Malinao (International Journal of Education Management and Religion, 2026)
Community-based tourism (CBT) has emerged as a sustainable alternative to mass tourism, prioritizing local empowerment, environmental preservation, and cultural integrity. The “1,000 Steps” in Sitio Nagtipunan, Sto. Domingo, Alfonso Lista, Ifugao, represents an emerging tourism destination that embodies these principles by promoting community engagement and environmental stewardship. Despite its natural beauty and cultural richness, the site’s viability as a CBT destination remains underassessed. Determining its alignment with the ASEAN Community-Based Tourism (CBT) Standard is essential to establish a sustainable tourism framework that enhances local livelihoods, fosters effective governance, and strengthens environmental management. The study aimed to assess the potential of the “1,000 Steps” as a CBT site by evaluating its performance based on ASEAN CBT dimensions. Employing a descriptive research design, data were gathered from 218 respondents, including residents, tourists, and local officials, through a structured and patterned questionnaire. Statistical tools, including mean, frequency, and percentage, were utilized in the data analysis. Results revealed strong community participation and transparent governance, high partnership effectiveness, and solid contributions to social well-being. Environmental conservation practices were positively rated, while tour and guiding services achieved the highest rating, reflecting both cultural sensitivity and visitor satisfaction. However, food and beverage services and management showed moderate adherence to standards, highlighting areas for improvement in hygiene and training. Findings confirm that active community involvement enhances the sustainability of tourism. Practically, the study provides an evidence-based framework for policymakers and planners to integrate ASEAN CBT standards into rural destinations, promoting inclusive, culturally grounded, and environmentally sustainable tourism development in the Philippines.